Dissociative episode and panic attacks triggered by pitolisant in a narcoleptic patient. (15th September 2022) - Brunetti, Valerio; Marotta, Jessica; Simoncini Malucelli, Giorgia; Marano, Giuseppe; Mazza, Marianna; Della Marca, Giacomo
Abstract : Pitolisant is a histamine 3-receptor antagonist/inverse agonist effective and safe for the treatment of excessive daytime sleepiness and cataplexy in narcolepsy. We report a 19-year-old woman affected by narcolepsy type 1 who presented panic attacks and dissociative symptoms induced by pitolisant. The patient medical history was unremarkable except that for familiarity for anxiety disorder and chronic insomnia. Moreover, a detailed psychometric evaluation revealed a profile of low resilience, a severe grade of depression, an anxiety trait and a propension to dissociative symptoms. Our report suggests that caution should be used in patients with predisposing factors to psychiatric disorders, especially during the first period of treatment with pitolisant. In consideration of the high prevalence of psychiatric comorbidities in narcolepsy, it seems worth to carefully investigate psychiatric background of narcoleptic patients.